Mechanical response of porcine hind leg muscles under dynamic tensile loading. (March 2021) - Wen, Yaoke; Zhang, Tingyu; Yan, Wenmin; Chen, Ye; Wang, Guanghua
Abstract: A modified split Hopkinson tension bar (SHTB) apparatus was used to investigate the dynamic tensile mechanical response of porcine muscles. A hollow aluminum alloy transmission bar and a semiconductor strain gauge were used to enhance the weak signal from porcine muscles. A ring-shaped copper pulse shaper was used to achieve stress equilibrium and constant approximate strain rates in the specimens. The thin muscle specimen, fixed by 3D-printed clamps, was warped around the bar ends to minimize the radial inertial effect during tensile loading. The quasi-static tests at strain rates of 0.1 s ∧ -1 were also conducted on a universal material testing machine to investigate the strain rate dependence. The true stress-strain curves of porcine muscle tissues along the fiber direction were determined at approximate strain rates of 800 s ∧ -1, 2000 s ∧ -1, and 3000 s ∧ -1. The experimental results show that the porcine muscle exhibits nonlinear, rate-sensitive, and orthotropic behavior. The Mooney–Rivlin model with two material constants was sufficient to represent the tensile response of porcine muscles at each strain rate. The rate-dependent Fields–Backofen model can describe the high strain rate response of the porcine muscles.